Strategi Perencanaan Komunikasi Sebagai Upaya Pengembangan Kapasitas dan Potensi Wisata di Desa Wisata Pipitan - Wiranata, Yuda; Sarwoprasodjo, Sarwititi; Hubeis, Aida Vitayala S (Jurnal Master Pariwisata (JUMPA); Volume 09, Nomor 01, Juli 2022DO - 10.24843/JUMPA.2022.v09.i01.p12, 2022)
Capacity building is needed as an effort to increase the capacity of community-based tourism actors. Community-based tourism is one of the alternative tourist destinations amid the many popular tourist destinations, especially in Indonesia. Problems that arise in community-based tourism management can be solved by means of communication. This research aims to find out the communication planning carried out by the Pipitan Tourism Conscious Group in increasing its capacity.  This research uses Philip Lesly's communication planning model with four stages, namely research and analysis, policy formulation, communication planning and communication activities.  This research data collection technique uses in-depth interviews with case study research methods. The results of the study explained in stages of analysis and research of the managers of Pipitan Tourism Village exploring tourism potential and getting some tourism potential such as Situ Ciwaka natural tourism, Blohok vegetable culinary tourism, religious tourism KH. Syuhari’s tomb and Pepetan wewe cultural tourism and debus. The stages of policy formulation for the tourism development program are submitted to the forum and decided during the deliberation of the work program at the beginning of each month. The stages of program planning divide the program by gender and age. The program for youth is a promotion on social media and for mothers, namely making handicrafts such as painting with cutting boards and frying pans. Finally, communication activities are Sunday night programs with the community, promotions on social media and also in collaboration with the Serang City Tourism Office for tourism promotion. Keywords: communication planning, capacity building, community-based tourism (cbt), pipitan tourism village banten.